Exposing Atlantic Salmon Post-Smolts to Fluctuating Sublethal Nitrite Concentrations in a Commercial Recirculating Aquaculture System (RAS) May Have Negative Consequences - Mortensen, Heidi S.; Jacobsen, Elin; Kolarevic, Jelena; Vang, Amanda (Frontiers in Animal Science, 2022)
Salmon farmers are interested in extending the time post-smolts are reared in recirculating aquaculture systems (RAS). However, there is a lack of knowledge regarding optimal water quality for post-smolts in RAS, and regarding potential consequences of long term exposure to different toxic compounds, such as nitrite, in the RAS water. To address this issue, we conducted a case study at a Faroese Atlantic salmon farm, that rears large post-smolts in fresh water RAS for 22 months before sea transfer, with no additional chloride salt, a known treatment for nitrite toxicity. The aim was to document the potential effects of long-term exposure of fluctuating sub-lethal nitrite concentrations in fresh water RAS on blood physiology of large post-smolts. The study was conducted over six weeks, at the end of the RAS production cycle. Our case study shows that after ~22 months in RAS with no additional chloride, the fish had accumulated a plasma nitrite concentration 8 to 16 times higher than the ambient water. Our results indicate that the accumulation may have resulted in extracellular hyperkaliemia, since there was a positive correlation between plasma nitrite and potassium levels (p=0.00095), with potassium levels almost twice as high than previously reported for Atlantic salmon. This could indicate that Atlantic salmon health is challenged due to prolonged sub-lethal nitrite exposure in fresh water RAS. Further research related to long-term nitrite exposure in RAS is needed to asses the potential negative impact, in order to optimize welfare and growth performance during production of Atlantic salmon post-smolts.